2015
DOI: 10.1136/vetreco-2014-000079
|View full text |Cite
|
Sign up to set email alerts
|

Use of tylvalosin in the control of porcine enzootic pneumonia

Abstract: ObjectivesThe purpose of this study was to investigate the efficacy of tylvalosin (Aivlosin Water Soluble Granules, ECO Animal Health) in drinking water for control of Mycoplasma hyopneumoniae (M hyo) on a farm with chronic enzootic pneumonia (EP) problems and high prevalence of mycoplasma-like lesions at slaughter.DesignOn a 4000-sow farm in the southeast of Spain, 1500 animals of same age were randomly divided into two groups: 900 pigs in the treated group (TG) and 600 pigs in the non-treated control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
1
13
2
1
Order By: Relevance
“…Despite the e cacy of M. hyopneumoniae vaccines in reducing lung lesions [26] and bacterial load from the respiratory tract [27], they are not capable to fully eliminate the bacteria from the animal giving rise to typical MLL in a variable percentage of pigs at abattoir in different countries [10,14,16,17]. To corroborate the usefulness of a mycoplasma-like scoring system to be adapted to abattoirs with a high number of slaughtered pigs per hour we investigated the prevalence of mycoplasma lung lesions in Spain and Portugal in a study with an elevated number of pigs (199,678) involving a high number of farms (221).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the e cacy of M. hyopneumoniae vaccines in reducing lung lesions [26] and bacterial load from the respiratory tract [27], they are not capable to fully eliminate the bacteria from the animal giving rise to typical MLL in a variable percentage of pigs at abattoir in different countries [10,14,16,17]. To corroborate the usefulness of a mycoplasma-like scoring system to be adapted to abattoirs with a high number of slaughtered pigs per hour we investigated the prevalence of mycoplasma lung lesions in Spain and Portugal in a study with an elevated number of pigs (199,678) involving a high number of farms (221).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is reported that the prevalence of mycoplasma-like lesions (MLL) at abattoir raging from 23.85% in Belgium to 72.60% in Germany, with a high variation among countries [9,10,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…hyopneumoniae infection affects especially growing pigs, causing significant economic losses in the swine industry worldwide, by chronic cough, growth retardation and predisposing animals to secondary infections [36]. Improvement of the management system and the environmental conditions of pig farms are essential parts of the control strategies just like vaccination and antibiotic treatment [4,7,8]. As vaccination alone is not always effective enough to prevent colonisation of the respiratory tract [9], antibiotic treatment might be necessary [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tylvalosin is currently used to control respiratory and enteric bacterial infections in poultry and swine against pathogens such as Mycoplasma sp. ( 43 , 44 ). Tylvalosin was recently found to exhibit anti-inflammatory properties by suppressing NF-κB, the transcription factor leading to the synthesis of potent pro-inflammatory mediators, such as CXCL-8 (also known as IL-8), in models of lipopolysaccharide (LPS)-induced pulmonary inflammation in mice or in piglets infected with Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) ( 42 ).…”
Section: Introductionmentioning
confidence: 99%